The effect of metal–insulator interface interactions on electrical transport in granular metals. (18th May 2022) - Gilbert, Simeon J; Rosenberg, Samantha G; Kotula, Paul G; Kmieciak, Thomas G; Biedermann, Laura B; Siegal, Michael P
Abstract: We present an in-depth study of metal–insulator interfaces within granular metal (GM) films and correlate their interfacial interactions with structural and electrical transport properties. Nominally 100 nm thick GM films of Co and Mo dispersed within yttria-stabilized zirconia (YSZ), with volumetric metal fractions ( φ ) from 0.2–0.8, were grown by radio frequency co-sputtering from individual metal and YSZ targets. Scanning transmission electron microscopy and DC transport measurements find that the resulting metal islands are well-defined with 1.7–2.6 nm average diameters and percolation thresholds between φ = 0.4–0.5. The room temperature conductivities for the φ = 0.2 samples are several orders of magnitude larger than previously-reported for GMs. X-ray photoemission spectroscopy indicates both oxygen vacancy formation within the YSZ and band-bending at metal–insulator interfaces. The higher-than-predicted conductivity is largely attributed to these interface interactions. In agreement with recent theory, interactions that reduce the change in conductivity across the metal–insulator interface are seen to prevent sharp conductivity drops when the metal concentration decreases below the percolation threshold. These interface interactions help interpret the broad range of conductivities reported throughout the literature and can be used to tune the conductivities of future GMs.